SERUM FERRITIN AS A PREDICTOR OF 30 DAYS MORTALITY IN PATIENTS OF DECOMPENSATED CHRONIC LIVER DISEASE - Umer, Naseer; Makki, Mujeeb Ullah; Kiran, Shagufta Kunwal; Jadoon, Nauman Arif (Journal of Ayub Medical College Abbottabad, 2017)
Background: Serum ferritin is marker for hepatic neco-inflammation and known 1 year mortality predictor in post-transplant patients. However, data on utility as early mortality predictor in patient of cirrhosis is scarce. We investigated whether ferritin can be used as one month mortality predictor in patients of decompensated cirrhosis. Methods: The study cohort included 132 patients in whom predictors of mortality were studied. Results: One hundred and thirty-two patients with 77 (58.33%) male with a mean age of 54 (±8.3) years with decompensated cirrhosis were followed for 30 days. enrolled for study. Majority of the patients had hepatitis C (71.4%) with 19 (14.3%) cases of hepatitis B related cirrhosis and 5.3%, 4.5% and 2.3% comprising alcoholic, autoimmune and Wilsons related decompensated cirrhosis respectively. Ninety-one (69.42%) patients were alive at end of study period, with serum ferritin levels were significantly different between the survivors and the non-survivors (p< .001) and showed significant correlation with CTP Score (p <.001) and MELD Score (p <.001). Regarding ferritin level and outcome, 76 (all alive) had ferritin level <200 ng/ml, 26 (13 alive, 13 died) had ferritin level between 200-400 ng/ml and 30 (2 alive, 28 died) had ferritin level >400 ng/ml (p= .001). With increasing ferritin level, CTP class as well as MELD score increased. Patients with raised ferritin levels were more likely to die compared to those with lower ferritin levels (p <.001). Conclusion: Serum ferritin levels correlate with severity of liver disease and are associated with early mortality in patients of decompensated cirrhosis independent of MELD score. Keywords: Ferritin; Predictor; Chronic liver disease